Kehidupan Sosial Ekonomi Pekerja Warung Remang- Remang di Desa Lasitae Kabupaten Barru - Rahmat, Rahmat; W. Suhaeb, Firdaus (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research was conducted to find out the social life of female workers after becoming a worker of dimly lit stalls in Lasitae Village, Barru Regency and to find out the economic life of female workers after becoming a worker of dimly lit stalls in Lasitae Village, Barru Regency The type of research used is descriptive qualitative using purposive sampling technique, namely data collection by means of observation, interview and documentation.In this study the data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the social life of dimang shop workers is divided into 2 indicators, namely: social environment and education, found while in the economic life of dimly lit shop workers are also divided into 2, namely: income and fulfillment of needs.